A description logic framework for commonsense conceptual combination integrating typicality, probabilities and cognitive heuristics. Issue 5 (2nd September 2020) - Lieto, Antonio; Pozzato, Gian Luca
ABSTRACT: We propose a nonmonotonic Description Logic of typicality able to account for the phenomenon of the combination of prototypical concepts. The proposed logic relies on the logic of typicality A L C + T R, whose semantics is based on the notion of rational closure, as well as on the distributed semantics of probabilistic Description Logics, and is equipped with a cognitive heuristic used by humans for concept composition. We first extend the logic of typicality A L C + T R by typicality inclusions of the form p :: T ( C ) ⊑ D, whose intuitive meaning is that 'we believe with degree p about the fact that typical C s are D s'. As in the distributed semantics, we define different scenarios containing only some typicality inclusions, each one having a suitable probability. We then exploit such scenarios in order to ascribe typical properties to a concept C obtained as the combination of two prototypical concepts. We also show that reasoning in the proposed Description Logic is ExpTime -complete as for the underlying standard Description Logic A L C .